Upaya Hukum Perlindungan Hak Desain Industri Produk Kaca Helm - Pratama, Aldiska Aqsyal; Putra, Fadhiel Ridho (Jurnal Analisis Hukum, 2025)
Intellectual property rights are an important aspect in the industrial world, especially in the manufacturing and product design industries. Along with increasing global competition, industry players are required to not only create functional products, but also have aesthetic value and visual uniqueness that can attract consumer interest. This research uses descriptive research methods and uses a juridical-normative approach, by examining related case studies that occur in the decision. This research was conducted with the aim of finding the main factors causing the KYT helmet industrial design dispute and knowing the legal considerations by the Supreme Court judges in Decision No. 147 K/Pdt.Sus-HKI/2024 regarding the basis for the plaintiff’s claim to cancel the rights of registered industrial designers. The factor that caused this dispute was the argument that the design did not fulfil the element of novelty because of the similarity at a glance with the industrial design of other products. The lawsuit filed did not have a strong legal basis because there was no legal effort to challenge the validity of the design within the stipulated time period, and the exclusive rights of the industrial design became part of the first party to register.